Management and Outcome of Traumatic Intracerebral Hemorrhage in 79 Infants and Children from a Single Level 1 Trauma Center - Harald Binder; Marek Majdan; Johannes Leitgeb; Stephan Payr; Robert Breuer; Stefan Hajdu; Thomas M. Tiefenboeck (MDPI AG, 2021)
Objective: Traumatic brain injury is a leading form of pediatric trauma and a frequent cause of mortality and acquired neurological impairment in children. The aim of this study was to present the severity and outcomes of traumatic intracerebral bleeding in children and adolescence. Methods: Seventy-nine infants and children with intracerebral bleedings were treated between 1992 and 2020 at a single level 1 trauma center. Data regarding accident, treatment and outcomes were collected retrospectively. The Glasgow Outcome Scale was used to classify the outcome at hospital discharge and at follow-up visits. CT scans of the brain were classified according to the Rotterdam score. Results: In total, 41 (52%) patients with intracerebral bleedings were treated surgically, and 38 (48%) patients were treated conservatively; in 15% of the included patients, delayed surgery was necessary. Patients presenting multiple trauma (p < 0.04), higher ISS (p < 0.01), poor initial neurological status (p < 0.001) and a higher Rotterdamscore (p = 0.038) were significantly more often treated surgically. Eighty-three percent of patients were able to leave the hospital, and out of these patients, about 60% showed good recovery at the latest follow-up visit. Overall, 11 patients (14%) died. Conclusion: The findings in this study verified intracerebral bleeding as a rare but serious condition. Patients presenting with multiple traumas, higher initial ISS, poor initial neurological status and a higher Rotterdamscore were more likely treated by surgery. Trial registration: (researchregistry 2686).